Evaluation of self-medication among students and professionals at a Medical school in southern Minas Gerais (Research, Society and Development, 2024)
Introduction: Self-medication is a widespread practice, especially among students and health professionals, who have easy access to medical information. The use of medicines without a prescription can led to significant risks, such as dangerous drug interactions, antimicrobial resistance and serious adverse effects. Objectives: The aim of this study was to survey the main aspects of self-medication among students and staff at a medical school in the south of Minas Gerais. Materials and Methods: This was a cross-sectional study that included data collection and subsequent comparative analysis between the groups observed. The findings were discussed with previously published and validated academic papers to obtain correlations between the scientific medical literature and the research findings. Results and Discussion: The results showed that 96.5% of the students and 84.2% of the staff reported using over-the-counter medication, with analgesics and anti-inflammatories standing out in both groups. However, the use of psychotropic drugs was more frequent among students, while staff used more muscle relaxants and anti-inflammatories. These data reflect the different academic and occupational pressures, revealing that although the groups have different contexts, both are vulnerable to self-medication. Conclusion: Self-medication among students and staff is worrying, due to the indiscriminate use of various classes of medication. Raising awareness and implementing educational policies are fundamental to minimizing the associated risks and encouraging safer and more responsible use of drugs.